Moods and emotions at work - Fisher, Cynthia D. (Henry Stewart Talks, 2012)
Defining moods and emotions, The affect circumplex, Dispositional affectivity, Affective events theory, Effects of dispositional affectivity at work, Effects of positive and negative moods and emotions at work, Emotional contagion, Emotional labor, Emotional intelligence, Research methods for affect at work